The Cheese Stands Alone: Situating the University of Waterloo within the Canadian Academic Library Landscape - Robichaud, Danielle; Byl, Lauren (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2022)
Despite a body of scholarly literature about the labour conditions of Canadian academic libraries/ians, little has been written about non-unionized Canadian librarians/archivists or the related historical and evolving labour environment at the University of Waterloo. Drawing on archival records and scholarly literature, this paper situates Waterloo within the Canadian academic library landscape in conversation with existing assumptions and understandings about academic and/or faculty status. It documents failed attempts at unionization and representation of librarians/archivists by the Faculty Association of the University of Waterloo (FAUW), the role of Waterloo administration in those outcomes, and the nature of, and changes to, the Librarian and Archivist Employment Handbook over time.